Research on edge offloading delay optimization of cellular networks based on optimal transport theory - Xiangyu LYU; Yong XIAO; Yi ZHONG; Qiang LI; Xiaohu GE (物联网学报)
With the development of the internet of things, a large number of user device (UD) were connected to cellular network.Since the changes in the spatial distribution of UD and application requirements, it is necessary to dynamically adjust the UD’ offloading decision.Comprehensively considering various parameter information in the networks such as the spatial distribution of UD, application requirements, and the processing capability of the edge servers on the base station (BS) side, the offloading decision of UD were optimized from the perspective of distribution.Based on the optimal transport theory, a delay optimization algorithm was proposed to reduce the average delay of the UD’ computing tasks offloading process by reasonably planning the offloading BS of the UD in the networks.The simulation results show that the average delay can be reduced by 81.06% using the proposed offloading mechanism based on delay optimization, and the traffic handled by each BS is balanced.